2020
DOI: 10.1021/acschemneuro.0c00476
|View full text |Cite
|
Sign up to set email alerts
|

(E)-3-Furan-2-yl-N-p-tolyl-acrylamide and its Derivative DM489 Decrease Neuropathic Pain in Mice Predominantly by α7 Nicotinic Acetylcholine Receptor Potentiation

Abstract: The main objective of this study was to determine whether (E)-3-furan-2-yl-N-p-tolyl-acrylamide (PAM-2) and its structural derivative DM489 produce anti-neuropathic pain activity using the streptozotocin (STZ)-and oxaliplatin-induced neuropathic pain animal models. To assess possible mechanisms of action, the pharmacological activity of these compounds was determined at α7 and α9α10 nicotinic acetylcholine receptors (nAChRs) and Ca V 2.2 channels expressed alone or coexpressed with G protein-coupled GABA B rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 33 publications
1
34
0
Order By: Relevance
“…[15,16], selective α7 nAchR antagonist methyllycaconitine (MLA; 6 mg kg −1 , i.p.) [17], Kv7 channel blocker XE991 (1 mg kg −1 , i.p.) [18,19], and σ 1-σ 2 agonist (method described below).…”
Section: Ddd-028 Administration and Study Of The Pharmacodynamic Mechanismsmentioning
confidence: 99%
“…[15,16], selective α7 nAchR antagonist methyllycaconitine (MLA; 6 mg kg −1 , i.p.) [17], Kv7 channel blocker XE991 (1 mg kg −1 , i.p.) [18,19], and σ 1-σ 2 agonist (method described below).…”
Section: Ddd-028 Administration and Study Of The Pharmacodynamic Mechanismsmentioning
confidence: 99%
“…Compelling evidence from our laboratory and others has demonstrated that activation of α7 nAchR could attenuate chronic pain, including neuropathic pain, inflammatory pain, and CIBP (Medhurst et al, 2008;Papke et al, 2015;Arias et al, 2020;Yang et al, 2021). Alsharari et al evaluated pain behaviors in the α7 mutant mice (KO) and α7 hypersensitive mice (KI) expressing the L250T α7 nAChR and their respective WT mice in chronic pain models (Alsharari et al, 2013).…”
Section: The Role Of α Nachr In Chronic Painmentioning
confidence: 99%
“…Moreover, α7 nAChR agonists and allosteric modulators suppressed the release of proinflammatory cytokines in chronic pain models (Loram et al, 2010;Sun et al, 2017). More importantly, α7 nAChR agonists and allosteric modulators have shown potent analgesic effects (Bagdas et al, 2018b;Quadri et al, 2018;Wang et al, 2019;Arias et al, 2020;Han et al, 2020). Therefore, it is plausible that potentiation of the α7 nAChR may be a promising therapeutic strategy for the management of chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…LL-00066471, JWX-A0108 (Sun et al, 2019), andJNJ-1930942 (Dinklo et al, 2011) improved acoustic startle reflex or genetic defects believed to be associated with hippocampal auditory gating. PAM2 (Arias et al, 2020), 1-(2',5 0 -dihydroxyphenyl)-3-(2-fluoro-4-hydroxyphenyl)-1-propanone (Perez de Vega et al, 2019), TQS (Abbas et al, 2017), and PNU-120596 (Bagdas et al, 2018b) were effective in models of inflammatory or neuropathic pain. Some PAMs are advancing toward Fig.…”
Section: A7-positive Allosteric Modulatorsmentioning
confidence: 99%